Development of Singapore's inward investment. - Chiam, Hui Yun. (2008)
The objective of this study is to investigate how both host and source countries’ characteristics influence the amount of FDI flow into Singapore. In addition, this study also seeks to analyze how Singapore has been successful in attracting FDI so that insights for future policy can be drawn.